Pedagogical and Professional Competencies of State Junior High School Science Teachers in Kendal District (Universitas Negeri Semarang, 2019)
The competence of science teachers in the teaching and learning process is an important factor in determining the success of the science teaching and learning process in schools. Science teachers must meet competency standards including pedagogical competencies and professional competencies.. This study aims to analyze the pedagogical and professional competencies of state junior high school science teachers in Kendal District. The type of research used is a mixed method using a sequential explanatory model. Quantitative and qualitative research is carried out sequentially, where qualitative data plays a role to prove, deepen, and expand quantitative data that has been obtained at an early stage. The source of the data came from 10 state junior high school science teachers (4 science teachers in accredited A, 4 science teachers in accredited B, 2 science teachers in accredited C) in Kendal District. Data collection in this study using questionnaire methods, interviews, tests, and documentation. The results showed that the competencies of state junior high school science teachers in Kendal District were in a fairly good category. The percentage level of pedagogical competence of science teachers is 73% and professional competence is 73%. Overall, the competencies of state junior high school science teachers in Kendal are included in the fairly good category with a percentage of 73%.